2020
DOI: 10.1002/mmce.22389
|View full text |Cite
|
Sign up to set email alerts
|

A low profile miniaturized widely‐spaced triband bandpass FSS using coupled resonance

Abstract: In this article, a triband highly selective widely-spaced bandpass frequencyselective surface (FSS) is presented. The proposed FSS is consisted of five metal layers that are separated from each other by four dielectric substrates. Using coupled resonance between layers, three passbands operating at 11.0, 17.4, and 31.9 GHz are achieved. Meanwhile, the dimension of the unit cell of the FSS can be achieved in 0.139λ 0 × 0.139λ 0 (λ 0 is the wavelength of the first resonant frequency in the free-space), and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…12,13 It performances a bandpass or band-stop effect due to the total reflection or transmission of EM waves in a certain frequency band. 14,15 As a filter, it is an excellent object to be select to broaden the absorption frequency band. 10,16 Through simulation, Li et al 17 sandwiched a square ring FSS between two magnetic materials, and found that the absorption bandwidth with the FSS is larger than that without the FSS.…”
mentioning
confidence: 99%
“…12,13 It performances a bandpass or band-stop effect due to the total reflection or transmission of EM waves in a certain frequency band. 14,15 As a filter, it is an excellent object to be select to broaden the absorption frequency band. 10,16 Through simulation, Li et al 17 sandwiched a square ring FSS between two magnetic materials, and found that the absorption bandwidth with the FSS is larger than that without the FSS.…”
mentioning
confidence: 99%
“…Considerable work has been done to obtain multi-band high-order bandpass filtering responses. By cascading multiple gridded-loop structures, References 17 19 designed a multi-band FSS with second-order filtering responses in each operating frequency band. However, the larger profile thickness and volume were the outcomes of the cascaded structure.…”
Section: Introductionmentioning
confidence: 99%